An extended graphical targeting technique for direct reuse/recycle in concentration and property-based resource conservation networks - Saw, Shin Yin (Animo Repository, 2011)
Minimum flowrate targeting methods for resource conservation networks (RCNs) have been developed over the last decades. The existing methodologies still have certain drawbacks. Their design insights could be deepened and some steps should be more convenient for the users. A targeting tool called the material surplus composite curve (MSCC), which is an improvement of the surplus diagram for water and hydrogen networks is introduced. The approach is illustrated on several cases selected from the literature. Using this technique, it is possible to determine rigorous flowrate targets for different variants of the RCN problem. © 2010 Springer-Verlag.